Soluciones a la Salud Mental Durante la Pandemia Covid 19 en la ciudad de Bogotá Colombia (2021)
The mental health public policy is aimed at improving the different actions to avoid damage to the psychological and economic aspects derived from symptoms such as anxiety and stress caused by the pandemic, seeking that health providers consider the potential of behavioral alternatives. of difficult situations in a social environment. Public policy was developed with the priority of saving lives by strengthening public health measures through hygiene and sanitation, through quality and health surveillance models protecting patients with chronic disease to reduce the high risk of mental health during the pandemic of covid 19. Among the findings found is that isolation, only affects the health and lives of people but also affects mental health, which is a disease perhaps just as dangerous as the virus, in addition to it. Covid 19 deepened inequality, poverty and economic and social vulnerability, increasing the already unacceptable gender gaps and the workload of paid and unpaid care, Among the main alterations that affect people's mental health, are the major disorders are anxiety and depression, it was found that public policy in mental health will be based on the prevention of mental disorders and comprehensive and integrated care in population.